A comparative analysis of judicial independence in Malaysia and The United Kingdom / Raja Mohamad Syahmi Raja Ismail ...[et al.] - Raja Ismail, Raja Mohamad Syahmi; Sidik, Mohd Sabidi Samsi; A. Malik, Emir Eizat; Mohamad Nor, Mohd Haswadi (2009)
The issue of judicial independence usually involves the question of whether the judiciary can exercise its duty without the interference of the other organ namely the executive and legislative under the doctrine of separation of powers. Since in Malaysia the doctrine of separation of power is not fully apply although there is separation of powers as according to the doctrine, each organ cannot interfere with the function of the other organs. Under this issue, with the amendment of article 121 (1) of federal Constitution, the reference to the judicial power was deleted as the judicial power that was vested to the high courts had been amended to be vested under the federal law. So it means that the judiciary has lost it power to exercise its duty without the interfering of the other organ. So, it shows that the judiciary power have been deprived by this amendment and the judiciary credibility can be questioned by the restraint of its power impose by the other organ. Now there are some measures taken by the government for the judicial reform in Malaysia to restore the judicial independence of the judiciary body in Malaysia. This research paper will then be discussing the judicial independence in Malaysia and United Kingdom regarding the legal aspect of the judicial independence and then will be comparing the comparative aspects of judicial independence of both countries with emphasizing more on what has been taken by the both country to ensure that judicial independence is being upheld. Apart from that, this research paper will also examine the issues and crisis that both governments faced with regards to upholding judicial independence.